Paint it blue : ACT art collection Siegfried Loch. - Weserburg Museum für moderne kunst, Bremen (Bremen München : ACT Music & Vision Gmbh München Weserburg Museum für moderne kunst Bremen, 2007)
Arroyo, Eduardo ; Baselitz, Georg ; Basquiat, Jean-Michel ; Berning, Anne ; Blohm, Bettina ; Brüning, Peter ; Bujnowski, Rafal ; Büttner, Werner ; Demand, Thomas ; Droese, Felix ; Fontana, Lucio ; Förg, Gunther ; Francis, Sam ; Geiger, Rupprecht ; Gertsch, Franz ; Girke, Raimund ; Graubner, Gotthard ; Gudmundsson, Sigurdur ; Guston, Philip ; Hafif, Marcia ; Hamak, Herbert ; Harrington, Mark ; Hiebert, Christine ; Horn, Rebecca ; Horn, Roni ; Immendorff, Jörg ; Jenssen, Olav Christopher ; Kelly, Ellsworth ; Klapheck, Konrad ; Klein, Yves ; McCracken, John ; Meyer, Jürgen ; Miyajima, Tatsuo ; Motherwell, Robert ; Nauman, Bruce ; Nay, Ernst Wilhelm ; Noel, Martin ; Oldenburg, Claes ; Ortins, David ; Pettibon, Raymond ; Picabia, Francis ; Piene, Otto ; Polke, Sigmar ; Richter, Daniel ; Richter, Gerhard ; Rose, Rolf ; Rothschild, Judith ; Ruff, Thomas ; Ruscha, Ed ; Schumacher, Emil ; Sturtevant, Elaine ; Welling, James ; Winters, Terry ; Zeniuk, Jerry
Exhibition "Paint it blue : ACT Art Collection Siegfried Loch", Weserburg Museum für moderne kunst Bremen, 10.03.2007 - 28.05.2007
Duits
boek